Drivers of highly diverse planktonic ciliate assemblages in peat bog pools from Tierra del Fuego (Argentina) - Kuppers, Gabriela Cristina (2016)
Peatlands often encompass shallow pools, wherein dystrophic and colored acid waters host a remarkably diverse biota, with ciliates likely playing a key role in their short trophic webs. In the Sphagnum magellanicum-dominated Rancho Hambre peat bog, a 2-year study was conducted in five pools with different morphometric and trophic characteristics, in order to identify main environmental variables driving ciliate species richness, abundance, biomass, and diversity. Overall species richness (125 taxa) was much higher than in northern Hemisphere counterparts. Deep minerotrophic pools hosted the richest communities, showing similar seasonal abundance patterns and the highest species turnover. Although all pools shared the same dominant ciliates, similarity in taxonomic composition among them was generally low (J = 0.22–0.35). Moreover, IndVal analysis showed that rare and occasional species were highly indicative of different pools. Euryoecious, heterotrophic species, occurred in all sites, while mixotrophs were typical from shallow ombrotrophic pools. Rimostrombidium hyalinum was the most indicative species of a deep ombrotrophic pool. A CCA revealed that the abundances of potential ciliate preys, i.e., picophytoplankton, bacterioplankton, and heterotrophic flagellates, were the most significant regulators of abundances of this group. Therefore, ciliate structure and dynamics were influenced by pool morphometry and physical and chemical features, but foremost by interactions with other plankton communities.